Issues of Improving Marketing Services In Agribusiness Enterprises (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The need to comprehensively use the whole system of generalizing and individual The article is devoted to the issues of improving marketing services in agribusiness enterprises, and it reveals the purpose and tasks of marketing services in agribusiness enterprises. Indicators evaluating the effectiveness of marketing services in agribusiness enterprises and their calculation procedure are explained. In addition, in order to increase the efficiency of agribusiness enterprises, scientifically based proposals and practical recommendations were developed for the further improvement of the field of marketing services for agricultural enterprises.